Recent progress in organic solar cells based on small molecules - Riede, M; Schueppel, R; Schulze, K; Wynands, D; Timmreck, R; Uhrich, C; Petrich, A; Pfeiffer, M; Brier, E; Reinold, E; Baeuerle, P; Leo, K (Society of Photo-Optical Instrumentation Engineers, 2008)
We report on a series of organic solar cells based on heterojunetions of oligothiophene derivatives with varying chain length and C60 fullerenes. Devices arc based on cither p-i-n or p-i-i structure. In the first the intrinsic photovoltaic active layer is sandwiched between a p-typc and n-typc doped organic wide-gap layer for hole and electron transport respectively. In the latter the electron transport layer is replaced by a thin layer of wide-gap material as exciton blocker. Through optimization of transport and absorber layers we are able to reach in devices with single heterojunetions an open circuit voltage Voc of about 1V, a short circuit current density Jsc of about 5.6mA/cm2 and a fill factor FF above 50% under an AM1.5 illumination with 1000W/m2. However, still only a small part of the available solar spectrum is used. Thus, based on these materials stacked solar cells have been made to further improve the light absorption. The thickness of each layer is optimized using optical simulations to match the currents delivered by each of the solar cells in the stack. Through the incorporation of a very efficient recombination zone between the stacked solar cells the resulting Voc nearly reaches the sum of the Voc of the two serially connected solar cells.